To find the expression for \( A \) that makes the equation true, we can simply evaluate the right-hand side of the equation:
\[ A = 5 - \frac{11}{3} \]
First, we need to convert 5 into a fraction with a denominator of 3. We can do this by writing 5 as \( \frac{15}{3} \):
\[ A = \frac{15}{3} - \frac{11}{3} \]
Now, we can subtract the two fractions:
\[ A = \frac{15 - 11}{3} = \frac{4}{3} \]
So, the expression for \( A \) that satisfies the equation \( A = 5 - \frac{11}{3} \) is:
\[ A = \frac{4}{3} \]